Comparison of DNA extraction efficiency between two commercial kits on whole blood, swab, and plasma samples - Minh Quan Hoang; Huu An Nguyen; Bich Huong Bui; Thuy Quynh Nguyen; Thuy Ngan Nguyen; Thi Phuong Nguyen; Thi Hoi Le; Tien Dung Pham (Vietnam Journal of Science, Technology and Engineering, 2025)
Whole blood, swab, and plasma samples are widely used in molecular biology testing in Vietnam. However, most DNA extraction kits currently in use are imported and rely on silica column technology, which can be challenging to integrate into automated or high-throughput workflows. To address this limitation, the MagBead PCG® DNA extraction kit (Phacogen) (PCG) was developed for DNA extraction from whole blood, swab, and plasma samples. Notably, the PCG kit is compatible with both manual and automated workflows across various automated systems. This study evaluated the performance of the PCG kit compared to the QIAamp DNA mini kit (Qiagen) (QIA) using 90 clinical samples, comprising 30 whole blood samples, 30 swab samples, and 30 plasma samples. DNA quality was assessed based on concentration, A260/280 purity, and real-time polymerase chain reaction (PCR) quantification of the beta-actin gene. Selected high-concentration samples were further analysed using agarose gel electrophoresis to evaluate DNA size and integrity. The results showed comparable DNA quality between the two kits, with no significant differences in concentration or purity. These findings indicate that the PCG kit performs equivalently to the QIA kit and is a cost-effective, reliable alternative for DNA extraction across diverse clinical samples in molecular biology applications.